Pesticides contamination and analytical methods of determination in environmental matrices in Malaysia and their potential human health effects – a review - Zaidon, Siti Zulfa; Ho, Yu Bin; Hashim, Zailina; Saari, Nazamid; Praveena, Sarva Mangala (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Pesticides application is essential in protecting crops and increases their productivity. However, this causes the pesticide residues to contaminate the crops and their surrounding environment that will eventually lead to exposure to human being. There is very little understanding on the human health effects of pesticides, thus many studies are being carried out for this purpose. In conjunction to this, there are various analytical methods on multi-residue pesticides analysis that have been developed over the years in various samples. This review provides an overview of the reported concentration of pesticides, the extraction and determination techniques of pesticides in environmental samples and the potential health effects they imposed on human in Malaysia from 2007 to 2017.